The association between childhood trauma and social support among Icelandic adolescent sexual perpetration - Guðbjörg Lilja Gylfadóttir 1987- (2017)
The fact that an adolescent can violate another child sexually is often overlooked. However, studies have indicated that a large portion of sexual perpetrators are under the age of 18 years old and at least 20% of reported rapes and molestations have been related to adolescent sexual offenders. This study was based on archival data from The Icelandic Centre for Social Research and Analysis (ICSRA), Youth in Iceland 2006. The sample used in this study consisted of 7,430 participants in 9th and 10th grades in secondary school in Iceland, with the gender ratio 49.9% male and 50.1% female. A logistic regression was performed to examine predictors of sexual perpetration. The main results in the study showed that those who were male, reported a history of sexual abuse, reported a history of physical abuse, had weaker parental support and weaker peer support were more likely to report sexual perpetration. Finally, by looking at an interaction effect between variables, for those who reported experiencing physical abuse, parental support was a weaker predictor for reporting sexual perpetration than for those that did not report physical abuse. Furthermore, peer support was a stronger predictor of answering the sexual perpetration question with a yes, for those that had experienced sexual abuse than those that had not. Keywords: adolescent perpetrator, peer support, parental support, sexual abuse, physical abuse Sú staðreynd að börn undir lögaldri geti brotið á öðru barni kynferðislega á það til að gleymast. Hinsvegar hafa rannsóknir sýnt að í 20% kynferðisbrotamála séu gerendur yngri en 18 ára. Í þessari rannsókn var notast við gögn frá Rannsóknum og greiningu þar sem börn í 9. og 10. bekk í grunnskóla á Íslandi svöruðu spurningum úr könnuninni Ungt fólk 2006. Þýðið samanstendur af 7,430 einstaklingum og þar af voru 49,9% karlkyn og 50,1% kvennkyn. Aðhvarfsgreining var notuð til þess að kanna forspárþætti um gerendur kynferðisofbeldis. Helstu niðurstöður rannsóknarinnar sýndu að þeir þáttakendur sem voru karlkyns og ...